PENGARUH BRAND IMAGE DAN PROMOSI TERHADAP KEPUTUSAN MAHASISWA PENDIDIKAN EKONOMI MEMILIH KULIAH DI UNIVERSITAS HKBP NOMMENSEN PEMATANGSIANTAR - Putri Yesi Siahaan; Anton Luvi Siahaan; Paulina Herlina N. Sirait (JOURNAL SAINS STUDENT RESEARCH, 2024)
The problem in this study is that there has been a decrease in the number of Economics Education students in 2020-2023. This study aims to determine the effect of brand image and promotion on the decision of Economic Education students to choose to study at HKBP Nommensen University Pematangsiantar.This research was conducted at HKBP Nommensen University Pematangsiantar. This type of research uses descriptive quantitative research methods. Where this method aims to describe the research results and draw conclusions. The population in this study were all students of Economic Education Stambuk 2020-2023, totaling 300 economic education students with the Random Sampling Technique and calculated using the Slovin formula. Data analysis techniques are carried out in several stages, namely data reduction, data presentation and drawing conclusions. Data collection techniques are carried out by observation, questionnaires (questionnaires), and documentation.From the results of data analysis, it shows that the brand image variable has an influence on the decisions of Economic Education students. Where the tcount value of the brand image variable (X1) is 3.394> t table 1.993 and the significance value is 0,01< 0,05. So it can be concluded that Ha1 is accepted. Promotion variables influence the decisions of economic education students. Where the tcount value of the promotion variable (X2) is -3.213> t table -1.993 and the significance value is 0,02 < 0,05. So it can be concluded that Ha2 is accepted. For the results of the F test (simultaneous), the Fcount value is 12.186> Ftable 3.12. So it can be concluded simultaneously that the brand image and promotion variables affect the decision variable. From these results it can be seen that Ha3 is accepted.